The influence of audit committee’s and company’s characteristic on intellectual capital disclosure - Zahroh Naimah; Nico Acintyo Mukti (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to test the influences of audit committee’s and company’s characteristic on intellectual capital disclosure (ICD) among the LQ45-listed companies in Indonesia Stock Exchange (BEI) between 2013 and 2014.The paper employed multiple linear regression and saturation sample as the analysis methods.The findings showed that size of audit committee does not significantly influence ICD; meeting frequency of audit committee positively influences ICD; and company size does not influence ICD positively. On the other hand, profitability does not significantly influence ICD; leverage has negative and significant influence on ICD; and the type of industry does not significantly influence intellectual capital disclosure.As there are few ICD studies, this research will surely add ICD antecedents to literature.